PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL KOOPERATIF TIPE TGT DI KELA IV SDN 14 KOTO LALANG KOTA PADANG - Laila Sari, Hafni; Tri Wulandari, Fikhen; Rasyid, Arwin; Etri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted in response to the low achievement in Social Studies among fourth-grade students at SDN 14 Koto Lalang. A considerable number of students failed to meet the Minimum Mastery Criterion (75), indicating that learning outcomes had not yet reached the expected standard. The issue was associated with teacher-centered instructional practices that limited student engagement and active participation. This research aimed to examine the effectiveness of the Teams Games Tournament (TGT) model in enhancing students’ learning outcomes and classroom involvement. The study employed Classroom Action Research using qualitative and quantitative approaches implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants included one teacher and 27 fourth-grade students in Padang. Data were collected through observation, tests, non-test instruments, and documentation. The findings were analyzed descriptively using percentage calculations and mean scores. The results demonstrated that the application of the TGT model improved instructional quality and significantly increased student engagement in group discussions, academic games, and tournament activities. Students’ average scores showed consistent improvement from the first to the second cycle, with most students achieving or surpassing the established criterion. In conclusion, the TGT model proved effective in improving Social Studies learning outcomes for fourth-grade students.